Modeling of energy system dataspace - Shakhovska, Natalia; Medykovskyi, Mykola (Publishing House of Lviv Polytechnic National University, 2011)
In this paper the model of an energy system dataspace is described. Описана модель простору даних енергетичної сфери.
Моделювання простору даних енергетичної сфери
Keywords: Dataspace; Datawarehouse; Integration Methods; Consolidation; Information Product